KOMPETENSI DIGITAL TATA USAHA DAN DAMPAKNYA PADA LAYANAN ADMINISTRASI KURIKULUM - Aulia Hafizoh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The rapid development of information and communication technology in the digital era has brought significant changes to the field of education, including curriculum administration. This study aims to analyze the digital competence of administrative staff and its impact on curriculum administration services at elementary school in Pekanbaru. The research employed a descriptive quantitative method with a survey approach. The population included all administrative staff, with purposive sampling used to select respondents experienced in utilizing digital technology. Data were collected through questionnaires and documentation observations, then analyzed using descriptive statistics and correlation analysis. The results indicate that the majority of administrative staff possess moderate to high digital competence, particularly in digital communication and data management (75%). This competence significantly affects administrative process efficiency, data accuracy, information accessibility, and data-based decision-making. However, the use of digital curriculum management applications still requires improvement through advanced training. These findings emphasize that digital competence not only accelerates and facilitates administrative tasks but also strengthens the role of administrative staff as strategic partners in decision-making. The study provides practical implications for enhancing staff capacity, providing training, improving infrastructure, and planning digital-based administration policies at elementary school in Pekanbaru.